An approach for the site selection of an interim storage facility for the reactor compartment of the decommissioned brazilian nuclear submarines - Maia, Yran Leite (2022)
The construction of the first Brazilian Nuclear-Powered Submarine (SN-BR) is scheduled to begin in 2022. At the end of its operational life, the submarine will be defueled and decommissioned. During the decommissioning process the reactor compartment (RC) is separated from the rest of the hull and sent to a temporary storage facility. Thus, Brazilian Navy (MB) has to design and build a facility capable of safe storing the RC for about 50 years to allow the decay of the activation radionuclides existing within this compartment. The site selection for the construction of the interim storage facility is one of the first step required to be performed. The purpose of this thesis is to propose a site selection process for the RC interim storage facility in Brazil. This site selection process is based on an Analytic Hierarchy Process methodology that takes into account nuclear and environmental national regulations, naval and shipyard specificities, and logistics constraints. The validation of the proposed site selection process was carried out by a case study that was able to identify six candidate sites that meet the established criteria and to rank them according to their degree of compliance with these criteria.